PROBABILITY OF ITZ PERCOLATION INFERRED BY SURFACE DENSITY AND SPATIAL DISTRIBUTION OF POLYDISPERSE AGGREGATE PARTICLES IN CONCRETE - SAKANO, Kosuke; IGARASHI, Shin-ichi (Cement Science and Concrete Technology, 2025)
The surface area and the mean free distance of aggregate particles in concrete were evaluated using the grading curves obtained by the sieve test and the image analysis for the particles that appeared in the cross-section of concrete. The aggregate-cement paste proximity was evaluated by the shell volumes of cement paste near aggregate particles. The number of fine aggregate particles was dominant in the total number of aggregate particles so the surface density of aggregate was almost determined by the fine particles. Therefore, the volume of the interfacial transition zone greatly depends on the presence of the fine particles. The volume ratio of the interfacial zone around aggregate particles to the entire volume of the cement paste matrix is relatively small based on the product of the measured surface density of aggregate and the shell thickness which is comparable to the mean diameter of cement particles. The mean free distance of aggregate particles was much larger than the size of cement particles. This fact suggests that the percolation of the ITZ to cover the entire cement paste matrix is not a realistic phenomenon in concrete. Taking account of the dispersion of many fine particles of aggregate, their random distribution results in both the clusters and the dispersed areas with a few particles. Thus, porous regions such as the interfacial transition zone are present in not only the vicinity of aggregate peripheries but also the bulk cement paste. Therefore, inhomogeneous regions with greater porosity could be considered as the statistical events that depend on the spatial packing density of aggregate and cement particles in the cement paste matrix. It is not necessarily formed on the surface of aggregate particles uniformly.